Biological Control of Fusarium oxysporum f.sp. cumini with Aspergillus versicolor - Israel, S.; Lodha, S. (Phytopathologia Mediterranea, 2005)
A native heat-tolerant strain of Aspergillus versicolor (Vuill.) Tirab. highly antagonistic to Fusarium oxysporum f. sp. cumini (Foc) was isolated from arid soils. In tests performed to ascertain its antagonistic activity against Foc as compared to Trichoderma harzianum, a 99.2 and 96.4% reduction in Foc propagules was achieved in A. versicolor and T. harzianum infested soil respectively. The reduction of Foc propagules in Foc and A. versicolorinfested soil was also determined. In a liquid-culture test, even at a low concentration of 0.5 ml cell-free filtrate, A. versicolor inhibited mycelial growth of Foc. Population changes of A. versicolor were examined at different soil moisture gradients, where maximum survival and multiplication of A. versicolor was estimated at 50% of moisture holding capacity. In general, with increasing concentrations of A. versicolor inoculum, soil population densities of Foc went down. Studies on thermal resistance showed that A. versicolor survived and multiplied even at 65°C. Soil amended with A. versicolor alone, or with a combination of T. harzianum and Verbisina enceloides residues was significantly better at reducing Foc than was non-amended control soil. A marked increase in the root length of cumin was observed in soil amended with A. versicolor or T. harzianum or both. The results suggest that A. versicolor has a potential value for use against Fusarium in hot arid soils because it can survive under dry and high-temperature conditions.